Pemodelan Struktur Permukaan 2D Kota Bengkulu Menggunakan Metode Geomagnet - Rama Ramdani; Refrizon Refrizon; Elfi Yuliza; Darmawan Ikhlas Fadli; Muhamad Hasan (Postgraduate, University of Mataram, 2023)
Research on 2D modeling of the subsurface structure of the Bengkulu city area was carried out using the geomagnetic method. In this study, we collected data from 130 measurement points using a set of Proton Procession Magnetometers (PPM) to obtain the total magnetic field value. The measurement data were processed by making corrections of daily variations and IGRF (International Geomagnetic Reference Field). We conducted data correction to contour the total magnetic field anomaly. After that, the contour of total magnetic field anomaly was used for the reduction to the poles. This research results from the total magnetic field anomaly show a pair of positive and negative closures. Cross-sections were made on the positive and negative closure pairs to determine the subsurface structure of the area by making a 2-dimensional (2D) model using Mag2DC software. The interpretation of the 2D modeling results shows that three rock layers are continuously arranged. The average susceptibility value of the first layer is 0.00001 cgs which is a sandstone layer at a depth of 0-400 meters; the second layer has an average susceptibility value of 0.002 cgs which is dominated by clay at a depth of 400-700 meters, and; the third layer has an average susceptibility value of 0.006 cgs which is a basalt rock layer at a depth of 700-1000 meters.